Defensible citadel: History and architectural character of the Lahore Railway Station - Naubada Ali; Zhou Qi (Frontiers of Architectural Research, 2020)
This study aims to investigate the defensible character of the Lahore railway station built in response to “the war of independence in 1857,” which greatly impacted the location and design of the building. This study demonstrates the integral role played by the railway station in the development of the new colonial city, which the British wants to be defensive in every aspect. Railways were introduced in Pakistan (India) soon after their inauguration in Britain. Beginning from the mode of transportation, the multifaced contribution of railways toward the urban growth, new architectural style, mode of construction, and technology cannot be recanted. The research is based on the documentation and analysis of the history of Lahore railway station design. First, this study uses primary and secondary data to offer a history of the Lahore railway station from its inception to final execution. Second, it explores the criteria adopted by the British for its site selection to make the station a defensible post. The research finding includes the visual features that enhanced the architectural character of the building. Qualitative methods are used including several other approaches, namely, literature review, archival data collection, analysis of photographs, and study of architectural drawings and old maps, to achieve the objectives.